ILRI in-house COVID-19 testing kit for use in sub-Saharan Africa - CGIAR Research Program on Livestock (2021)
Testing showed a high concordance between the ILRI in-house reconstituted kit and the commercial kits (Da An Gene and TaqPath). The validation assay has demonstrated that the ILRI kit can be used as an alternative to the commercial assay kits for the RT-qPCR diagnosis of SARS-CoV2.